Factors Influencing of College Students’ Choice to Abroad: A Survey Study - Karki, Bikram (International Research Journal of MMC, 2024)
This study aims to identify the factors of college students’ choices to migrate abroad. The independent variables are push and pull factors and the dependent variable is the socio-economic motive for going abroad. Push factors consist of unemployment, poverty, family conflict, an inferior education system, political disturbance, and poor development activities, and pull factors consist of the desire to study, fashion, earn and learn, be rich, relative invite, and friends' suggestions. The study is carried out using a survey research design. The nature of the study is descriptive. For this study, data were collected from primary sources. The researchers obtained data about the sample using answers to structural questionnaires from the sampled 110 bachelor-level students of the Gaurishankar Multiple Campus, Charikot Multiple Campus, and Hanumanteshwor Multiple campus of Dolkahal district. Descriptive and inferential statistics were applied for the data analysis using SPSS software version 23. According to respondents from the descriptive analysis, most college students were unsatisfied with Nepal's current political system and government intervention for socio-economic development. This research found that push and pull factors were significant determinants but push factors are more important than pull factors to motivate migration. Thus, three-tier governments should increase the budget for higher education for quality education and productive sectors with research.